HIGH PREVALENCE OF JOHN CUNNINGHAM VIRURIA IN RENAL TRANSPLANT RECIPIENTS (Iraqi Journal of Medical Sciences, 2017)
Background: John Cunningham virus (JCV) is one of the important viruses in immunocompromised patients. High JC viruria is seen in kidney allograft recipients; some of them with a polyomavirus associated nephropathy (PVAN) just like BK polyomavirus but to a lesser extent.Objective :To detect JCV viruria in a sample of Iraqi renal transplant recipients, and its association with renal function.Methods: A prospective study enrolled 71 renal transplant recipients (RTR) and 20 normal donors (ND) as controls. Urine samples were collected from all RTR and ND. Viral DNA was extracted from 1 ml urine samples, and then, JC virus DNA was detected and measured by Taqman quantitative real-time PCR.Results: Out of 71 RTRs, 31 (43.66%), and 2 out of the 20 (10%) controls had positive JC viruria. The mean JCV viruria was 6.8 x104, and 1.04x103 copies/ml for RTRs and controls respectively.Conclusion: There is a relatively high prevalence of JCV viruria in Iraqi RTR patients.Keywords: JC virus, renal transplantation, urine, real-time PCR. Citation; Mervit B. Jasim, Ali J.H. Al-Saedi, Mustafa R. Hussein, Asmaa B. Al-Obaidi, Haider S. Kadhim. High prevalence of John Cunningham viruria in renal transplant recipients. Iraqi JMS. 2017; Vol. 15(2): 108-115. doi: 10.22578/IJMS.15.2.2
Keywords: JC virus; renal transplantation; urine; realtime PCR